Działalność prof. Antoniego Knota w organizacji bibliotekarstwa naukowego na Dolnym Śląskuw latach 1945-1956 = The activities of Prof. Antoni Knot connected with the organizing of scholarly librarianship in Lower Silesia in the years 1945-1956 - Firlej-Buzon, Aneta (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Social life in the Western and Northern Territories granted to Poland as compensation for areas incorporated into the territory of the Soviet Union had to be organized from scratch, practically from the moment of the arrival of the first Poles in the Second District, Lower Silesia. Thanks to the talent, work and the great sacrifice of Wrocław?s pioneers, this ?foreign city? was quickly raised from its ruins, and cultural, scholarly and educational establishments were opened. Despite the total absence of Polish books, as well as severe staff shortages, the University Library and the Technical University in Wrocław were quickly opened, serving the incoming student community and academic staff. In 1946, a part of the historical resource of the National Ossolińscy Institute was brought to the town, to contribute to strengthening the relationship between the Western Lands and the rest of the country. For persons displaced from Lviv (Polish Lwów), the placing of these collections in Wrocław held a special significance. The search for and recovery of cultural goods ? including books ? removed and hidden in Lower Silesia, the organization of scientific collections, the development of the legal basis for the development of the Library of the University of Wrocław and the National Ossolińscy Institute, and finally, the concern for the academic preparation of library staff, were all accomplishments associated with that great lover of books Professor Antoni Knot.
Keywords: Knot, Antoni (1904-1982); biblioteka uniwersytecka; Politechnika Wrocławska; dobra kultury; Narodowy Instytut Ossolińskich; bibliotekarstwo; University Library in Zielona Gora; Wrocław University of Science and Technology; cultural goods; National Ossoliński Institute; librarianship